2018
DOI: 10.1002/jcp.27800
|View full text |Cite
|
Sign up to set email alerts
|

Downregulated microRNA‐330 suppresses left ventricular remodeling via the TGF‐β1/Smad3 signaling pathway by targeting SRY in mice with myocardial ischemia–reperfusion injury

Abstract: microRNAs (miRs) are essential in the development of heart failure. The aim of this study is to investigate the effect of microRNA‐330 (miR‐330) on left ventricular remodeling via the TGF‐β1/Smad3 signaling pathway by targeting the sex‐determining region Y (SRY) in mice with myocardial ischemia–reperfusion injury (MIRI). Differentially expressed gene (DEG) in myocardial ischemia–reperfusion (IR) was screened out and the miR that targeted the DEG was also predicted and verified. A model of MIRI was established … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…A recent study reported that miRNA-330 overexpression in Alzheimer's disease contributed to the reduction of amyloid β, oxidative stress, and mitochondrial dysfunction by targeting VAV1 through the MAPK pathway (Zhou et al, 2018). In addition, downregulated miRNA-330 could reduce myocardial infarction size through suppressing left ventricular remodeling (Liu Z. Y. et al, 2019). The discrepancy in miRNA-330 biological effects may result from the different diseases, tissues, and experimental conditions used.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that miRNA-330 overexpression in Alzheimer's disease contributed to the reduction of amyloid β, oxidative stress, and mitochondrial dysfunction by targeting VAV1 through the MAPK pathway (Zhou et al, 2018). In addition, downregulated miRNA-330 could reduce myocardial infarction size through suppressing left ventricular remodeling (Liu Z. Y. et al, 2019). The discrepancy in miRNA-330 biological effects may result from the different diseases, tissues, and experimental conditions used.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that the TGF-β/Smad3 signaling pathway was activated and promoted ventricular remodeling after IR injury in rats (17), while mediating the protection of myocardial cells against IR injury via the stimulation of sphingosine-1-phosphate (S1P)/S1P receptor 1. TGF-β1/Smad3 has also been reported to exert an important effect on cerebral ischemia.…”
Section: Aggravation Of Hepatic Ischemia-reperfusion Injury With Increased Inflammatory Cell Infiltration Is Associated With the Tgf-β/smmentioning
confidence: 99%
“…The MI mouse model was established in accordance with a previous study [18] and speci c methods were illustrated as follows. Healthy adult C57BL/6 mice of the same age were purchased from Beijing Beike Huaxia Biomedical Technology Co., Ltd. [SYXK (Beijing) 2017-0044, Beijing, China].…”
Section: Establishment and Grouping Of MI Micementioning
confidence: 99%
“…The cardiac function of mice and its correlation with the above indexes were analyzed. TTC staining TTC staining method was as previously mentioned [18]. Following TTE, the hearts were taken out from the mice and frozen for half an h at -80°C, and then the transverse section across the left ventricular long axis from the apex to the bottom was obtained using a vibrating blade.…”
Section: Transthoracic Echocardiography (Tte)mentioning
confidence: 99%
See 1 more Smart Citation